Ripening-Dependent Changes in Antioxidants, Color Attributes, and Antioxidant Activity of Seven Tomato (Solanum lycopersicum L.) Cultivars - Shiva Ram Bhandari; Jun Gu Lee (Journal of Analytical Methods in Chemistry)
To evaluate the ripening-dependent changes in phytonutrients, seven commercial cultivars (two general and five cherry) of tomatoes were cultivated under greenhouse conditions. Fruits were harvested at breaker, turning, pink, light red, and red stages of each cultivar, and antioxidant contents, color attributes, and antioxidant activities were measured. During ripening process, lycopene content increased from the breaker to red stage, while lutein displayed the reverse accumulation pattern, with higher values during the breaker stage. In contrast, β-carotene showed the highest levels of synthesis in pink and light red stages. Furthermore, flavonoids (quercetin, rutin, naringenin, and luteolin) also showed similar ripening-dependent changes, with higher quantities in pink and light red stages. Ascorbic acid showed continuously increasing patterns throughout ripening until the red stage, while the accumulation of total phenolics was cultivar-dependent. These results indicate that each antioxidant compound has a unique pattern of accumulation and degradation during the ripening process. “Unicon” exhibited highest total carotenoid (110.27 mg/100 g), total phenol (297.88 mg GAE/100 g) and total flavonoid content (273.33 mg/100 g), and consequently highest antioxidant activity (2552.4 μmol TE/100 g) compared to other cultivars. Throughout the ripening processes, total phenolics showed the highest correlation with antioxidant activity, followed by β-carotene and total flavonoids. In conclusion, ripening in tomatoes is accompanied by incremental increases in various antioxidant compounds to some extent, as well as by concomitant increases in antioxidant activity.